Does modularity of metal-on-metal hip implants increase cobalt: chromium ratio?. Issue 1 (January 2021) - Ilo, Kevin C; Aboelmagd, Karim; Hothi, Harry S; Asaad, Asaad; Skinner, John A; Hart, Alister J
Background: Blood metal ion levels are used in the surveillance of metal-on-metal (MoM) hip implants. Modular implants contain an extra source of metal debris that may affect the ratio of metal ions in the blood. Methods: This was a retrospective study of 503 patients with hip replacements made by a single manufacturer (Smith & Nephew, Warwick, UK) with the same bearing surface. There were 54 total hip arthroplasties, 35 Birmingham Mid-Head Resections and 414 hip resurfacings. Whole blood metal ion levels and their ratios were analysed to investigate the effect of a modular junction. Results: The cobalt:chromium ratios were greater in the total hip arthroplasty group (mean 2.3:1) when compared to the resurfacings group (mean 1.3:1, p  = <0.05) and Birmingham Mid-Head Resection group (mean 1.1:1, p  = 0.11). Conclusions: This study demonstrated a trend for a higher cobalt:chromium ratio in patients with MoM total hip replacement that may be due to metal debris from the modular stem-head junction. Further work is required to correlate clinical data with retrieval analysis to confirm the effect of taper material loss on the cobalt:chromium ratio.